UTILIZATION ANALYSIS OF E-COMMERCE (Case Study At Surabaya Football Store, Surabaya ) - Danang Purboyo (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
The Developments in science and technology led to a change of society culture in daily life, with the creation of an openness and transparency in various fields, especially in the field of information technology and management. Speed of information needed by the community, including the world of communication and business. Information technology and management developed rapidly in Indonesia. This phenomenon can be seen with the increasing user of the Internet in Indonesia from year to year. According to the version of the office of the Ministry of Communications and Informatika in 2012, Indonesia ranks second in the world's Internet users, Indonesia ranks second in the world's Internet users. China is ranked first. The use of technology is expected to provide substantial benefits to the competitive business world. The Companies that are able to compete in the competition is a company that is able to implement technology into the company. One type of technology implementation in terms of increased business competition and product sales is by using electronic commerce (e-commerce) to market a variety of products or services. In other words, e-commerce will become a powerful alternative business infrastructure on current and emerging information age. E-commerce is a new land to generate and exploit that promotes business effectiveness in implementation.This fact proves that e-commerce has an important role in helping to increase sales turnover, the efficiency of the entire labor and operational costs that need to be released to manufacturing and marketing. The Increasing of the competition, Indonesia requires businesses continuously improve efficiency, improve product quality, service and innovation. Business on the Internet has a big impact in different types of companies. So is the company's manufacturing and services is growing dramatically as more consumers are shopping via the Internet. Due to the convenience and benefits offered by this new way of business, many companies take towards business online. In conducting the study required a research method adapted to the subject matter to be studied. By using appropriate research methods it will get the data and information to support research so that the scope of the research scope of the study will be more clear and focused. Based on the research to be conducted, the research method used was qualitative research. To the future for Surabaya Football Store In order to facilitate the management in monitoring the course of the company's operations will require a special section dealing with the internal control of the company, because in this section has the responsibility to oversee all parts. Keywords: E-commerce, Analysis